Age and Perioperative Outcomes After Implementation of an Enhanced Recovery After Surgery Pathway in Women Undergoing Major Prolapse Repair Surgery. Issue 2 (February 2021) - Carter-Brooks, Charelle M.; Romanova, Anna L.; DeRenzo, Joseph S.; Shepherd, Jonathan P.; Zyczynski, Halina M.
Abstract : Objective: As perioperative care pathways are developed to improve recovery, there is a need to explore the impact of age. The aim of this study was to compare the impact of a urogynecology-specific enhanced recovery after surgery (ERAS) pathway on perioperative outcomes across 3 age categories: young, middle age, and elderly. Methods: A retrospective cohort study was conducted assessing same-day discharge, opioid administration, pain scores, and complications differences across and within 3 age categories, young (<61 years), middle age (61–75 years), elderly (>75 years), before and after ERAS implementation. Results: Among 98 (25.7%) young, 202 (52.9%) middle-aged, and 82 (21.5%) elderly women, distribution before and after ERAS implementation was similar. In each age category, we found a commensurate increase in same-day discharge and decrease in length of stay independent of age. Age was associated with a variable response to opioid administration after ERAS. In women who received opioids, we found there was a greater reduction in opioids in elderly. Young women received 22.5 mg more than middle-aged women, whereas elderly women received 24.3 mg less than middle-aged women ( P < 0.0001, P < 0.0001) for a mean difference of 46.8 mg between the youngest and oldest group. We found no significant differences in postanesthesia care unit pain scores with ERAS implementation. Complications did not increase after ERAS implementation in any age group, although younger and elderly women were more likely to experience complications independent of ERAS. Conclusions: Elderly women had similar outcomes compared with their younger counterparts after implementation of an ERAS pathway. Further research is needed to assess whether our age-related observations are generalizable.